Emotion and Behavior - Paul Pauli; Fritz Strack; Peter Weyers (Frontiers Media SA, 2016)
In this Research Topic, several groups of researchers from both social and biological psychology summarize their findings addressing the relation between emotion and behavior. The Reflective-Impulsive Model (RIM) (Strack & Deutsch, 2004; 2014 in press) serves as a general orientation and provides a link to integrate the results from seemingly divergent perspectives. The contributions focuses on different types of emotional behaviors, like facial expressions and impulsive reactions. They address the central issue of approach vs. avoidance and include clinical topics like addiction and fear. Methodologically, the contributions are predominantly experimental and are partly based on manipulations in the context of virtual reality.
English
Keywords: impulsive; emotion; reflective; Behavior; avoidance; approach